FEATURE EXTRACTION METHODS FOR IC CHIP MARKING INSPECTION-A COMPARISON - Nagarajan, R.; Yaacob, Sazali; Pandian, Paulraj; Rizon, Mohamed; M.Karthigayan, nan (Iraqi Journal for Electrical and Electronic Engineering, 2006)
In this paper, an Industrial machine vision system incorporating Optical Character Recognition (OCR) is employed to inspect the marking on the Integrated Circuit (IC) Chips. This inspection is carried out while the ICs are coming out from the manufacturing line. A TSSOP-DGG type of IC package from Texas Instrument is used in the investigation. The inspection has to identify the print errors such as illegible character, missing characters and up side down printing. The vision inspection of the printed markings on the IC chip is carried out in three phases namely image preprocessing, feature extraction and classification. Projection profile and Moments are employed for feature extraction. A neural network is used as a classifier to detect the defectively marked IC chips. Both feature extraction methods are compared in terms of marking inspection time.